Gendered Framing in Political Campaign Coverage: A Content Analysis of Selected Nigerian Newspapers - Luka, Luka Joshua; Ugondo, Peter (International Journal of Humanities, Education, and Social Sciences, 2025)
This study investigates the gendered framing of political campaigns in selected Nigerian newspapers, with a focus on how media narratives shape public perceptions of male and female political candidates. Utilizing content analysis as the primary methodology, the research examines 120 newspaper articles, 30 each from The Punch, The Guardian, Vanguard, and ThisDay. The objective is to assess the nature of media representations and their implications for gender equity in political participation. The findings reveal a persistent pattern of stereotypical framing that reinforces traditional gender norms, often portraying female candidates in terms of their personal lives, emotional attributes, or appearance, while male candidates are predominantly framed around competence, leadership, and policy issues. This imbalance in representation contributes to the marginalization of women in political discourse and may serve as a barrier to their full participation in the political process. The study offers critical insights into media bias and underscores the need for more gender-sensitive media policies and practices. It contributes to the broader discourse on media influence, political representation, and the intersection of gender and journalism in Nigeria.